RISK PROFILING OF SECONDARY EQUITY INVESTORS FROM THE CHENNAI CITY OF INDIA BASED ON THE BIG FIVE PERSONALITY MODEL - Renu Isidore; C. Joe Arun (Copernican Journal of Finance & Accounting, 2022)
The risk taken by the investor depends on several independent variables like: personality, biological age, investment experience and income. The main aim of this article is to combine all these variables in order to build an exhaustive risk profile on the basis of the Big Five Personality dimensions. The research method applied is exploratory in nature and questionnaire survey method was employed to gather data from 436 secondary equity market investors residing in the Chennai city of India. ANOVA was employed to develop the risk profile. The outcome of the research was an exhaustive risk profile combining all the related variables and a regression model predicting the equity returns. The main conclusions of the study are that the investors with the more of the conscientiousness personality tend to take less risk. This finding was also consistent among the senior investors, high income investors and those with mediocre/ high investment experience. The study also concluded that the agreeable investors with high income/high investment experience, tend to take less risk. Only the young investors with more of the conscientiousness personality tend to take more risk and with more of the extraversion personality tend to take less risk. This study serves as a guidance for advisors to provide appropriate recommendations on the basis of the risk appetite and personality of the investors.